Paraiso travel - Lluch, Rafa; Correa, Aldemar; Reguera, Ana de la; Blandon, Angelica; Francisco, Margarita Rosa de; Leguizamo, John 1964-; Rendon, Juan; Franco, Jorge 1962- (Filmax Home Video, 2008)
Marlon Cruz, a young Columbian man who, motivated by his beautiful girlfriend Reina leaves his life in Columbia to illegally cross the border and find fortune in New York. Marlon's journey, which takes him to through seedy strip clubs, dance halls, homeless hostels, and the streets of Jackson Heights, ultimately takes him to a place he could have never predicted